The role of aryl hydrocarbon receptor in vitiligo: a review - Li, Yiting; Zeng, Yibin; Chen, Zile; Tan, Xi; Mei, Xingyu; Wu, Zhouwei (Frontiers in Immunology, 2024)
Vitiligo is an acquired autoimmune dermatosis characterized by patchy skin depigmentation, causing significant psychological distress to the patients. Genetic susceptibility, environmental triggers, oxidative stress, and autoimmunity contribute to melanocyte destruction in vitiligo. Due to the diversity and complexity of pathogenesis, the combination of inhibiting melanocyte destruction and stimulating melanogenesis gives the best results in treating vitiligo. The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that can regulate the expression of various downstream genes and play roles in cell differentiation, immune response, and physiological homeostasis maintenance. Recent studies suggested that AhR signaling pathway was downregulated in vitiligo. Activation of AhR pathway helps to activate antioxidant pathways, inhibit abnormal immunity response, and upregulate the melanogenesis gene, thereby protecting melanocytes from oxidative stress damage, controlling disease progression, and promoting lesion repigmentation. Here, we review the relevant literature and summarize the possible roles of the AhR signaling pathway in vitiligo pathogenesis and treatment, to further understand the links between the AhR and vitiligo, and provide new potential therapeutic strategies.